Vamos ao museu hoje?: lazer e educação em visitas mediadas - Romilda Aparecida Lopes (2015)
This research aimed to investigate and analyze the articulation between education and leisure during the preparation and development of mediated tours in museums of Juiz de Fora, Minas Gerais, through the eyes of their managers and mediators. Also, we aimed to understand the logic and peculiarities which structured and supported such practices. Of a qualitative approach, the methodology of this study had as a basis the development of a bibliographical investigation, participant observation, and through semi-structured interviews with 10 volunteers, including mediators and managers of the two museums of the city. The participant observation took place during the mediated tours, as well as with my participation on sporadic days. It is important to mention that the field research and the analysis of information were based on the logic exposed by Boaventura de Sousa Santos (2006), making use, mainly, of the paper entitled: For a sociology of absences and a sociology of emergences, in which the author proposed three sociological procedures which support a new rationality, which he classifies as: the sociology of absences, the sociology of emergences and the translation work, whose procedures have as main goal the expansion of the present and contraction of the future. The results highlight that, in museums, leisure and education, there are well-defined outlined peculiarities, which are guided in accordance to the different interests and intentions attributed to them. The subjects use leisure and education for the development of actions within the walls of the museum, following the guidelines present in the experienced context, being permeated by values, ideologies, hegemonies, political disputes, liberty and submission, characterizing, thus, a socially constructed and situated experience. The ways which experiences of leisure and education follow during the mediated tours reflect the desire of a time and the aspirations stemmed from historically defined moments. It was possible to observe that the relation leisureeducation in mediated tours in the museums visited, through the eyes of managers and mediators, show the production of non-existences based on monocultural logics, that is, principles and attitudes which can originate theories and practices that are domiant and farsided, since, in some moments they envision a reduced part of the reality of museums. In this sense, it was possible to learn that the relation leisure-education, from the conceptions of those interviewed, reproduce entrenched dichotomies in notions of obligatoriness and nonobligatoriness; productive and improductive; time to learn and time for leisure. As to what concerns the logics which guide the mediated tours, it was possible to perceive that notions of privileged space, sacred space and time for knowledge reproduce notions that, in many cases, privilege the transposition of knowledge, the productivity, and the raise in number of visitors, the segmentation of time and naturalization of differences. However, it was possible to learn that the logics, when contrasted with the ecologies proposed by Santos (2006), reveal other possibilities and relations, allowing for exchanges. This way, leisure and education, when seen through the prism of ecologies, can be considered allies for the experiences which take place in museums, or if they cannot, they would serve as centers of power and domination.